2009
DOI: 10.1111/j.1532-5415.2009.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster‐Randomized Trial of an Educational Intervention to Reduce the Use of Physical Restraints with Psychogeriatric Nursing Home Residents

Abstract: An educational program for nursing staff combined with consultation with a nurse specialist (RN level) had no effect on the use of physical restraints with psychogeriatric nursing home residents. In addition to restraint education and consultation, new measures to reduce the use of physical restraints with psychogeriatric nursing home residents should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 28 publications
5
110
0
2
Order By: Relevance
“…The results of these studies are conflicting: some reported positive effects (Evans et al, 1997;Testad et al, 2005), while others found no effect (Evans et al, 1997;Huizing et al, 2006;Testad et al, 2010). Recent studies confirmed that education alone is not enough to ensure a reduction in the use of restraints (Huizing et al, 2009a;Pellfolk et al, 2010;Testad et al, 2010). The availability of alternative interventions seems to be an important additional prerequisite for eliminating restraint use (Becker et al, 2003;Capezuti et al, 1999;Freeman, 2004;Hoffman et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…The results of these studies are conflicting: some reported positive effects (Evans et al, 1997;Testad et al, 2005), while others found no effect (Evans et al, 1997;Huizing et al, 2006;Testad et al, 2010). Recent studies confirmed that education alone is not enough to ensure a reduction in the use of restraints (Huizing et al, 2009a;Pellfolk et al, 2010;Testad et al, 2010). The availability of alternative interventions seems to be an important additional prerequisite for eliminating restraint use (Becker et al, 2003;Capezuti et al, 1999;Freeman, 2004;Hoffman et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…It is still commonly argued that physical restraints protect patients and their environment from serious injury caused by aggressive behavior against others and autoaggressive behavior (Strumpf and Tomes, 1993;Hamers et al, 2004;Testad et al, 2010). Although there is no evidence for the beneficial effects of restraint use, these opinions clearly hinder the reduction or prevention of restraint use in clinical practice Huizing et al, 2009). However, evidence shows that when nursing home residents are being physically restrained, cognitive performance, mood and social engagement suffer (Castle, 2006).…”
Section: Physical Restraints: Their Effect On Physical Activity Cognmentioning
confidence: 98%
“…The commonest type of restraint used in acute and residential care settings is still the bed rail [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These include wandering, aggression and interference with medical equipment. 3 The use of physical restraint in both acute and longterm care settings is not supported by evidence of efficacy or safety. Thus, the decision to use an intervention of little proven benefit, but which has the potential to cause harm, has clear ethical, legal and clinical implications.…”
mentioning
confidence: 99%